Model and data engineering : 6th International Conference, MEDI 2016, Almería, Spain, September 21-23, 2016, Proceedings /: 6th International Conference, MEDI 2016, Almería, Spain, September 21-23, 2016, Proceedings. (2016) - Unknown
No abstract available